Curcumin-Based Anti-Prostate Cancer Agents - Chen, Qiao-Hong (Anti-Cancer Agents in Medicinal Chemistry, 2015)
Prostate cancer possesses the highest occurrence rate and is the second-paramount disease that causes canceraffiliated death among men in the United States. Approximately 30,000 men die each year of castration-resistant prostate cancer due to the inevitable progression of resistance to first-line treatment with docetaxel. The safety profile of dietary curcumin in humans has been well-documented, and its therapeutic prospect in treating prostate cancer, especially for castration-resistant prostate cancer, has been evidenced in several cell culture systems and human xenograft mouse models. The critical disadvantage of curcumin as a drug candidate is its low bioavailability caused by poor water solubility and rapid in vivo metabolism. Curcumin is characteristic of regulating multiple targets, representing a good example for the philosophy to search for multitargeted drugs in the realm of drug design and drug development. This feature, together with its potential in treating castration-resistant prostate cancer and its safety profile, enables curcumin to serve as an ideal lead compound for the design and syntheses of curcuminbased agents with improved potential for the clinical therapies of prostate cancer. Several researches aiming to improve its bioavailability and potency resulted in the discovery and development of a wealth of curcumin-based compounds with an enhanced anticancer potential and/or an improved pharmacokinetic profile. This review starts with a brief summarization of the prospect of curcumin in treating prostate cancer and its mechanisms of action, then provides an in-depth overview of current development of curcumin-based anti-prostate cancer agents and their structure-activity relationships, and ends with the syntheses and pharmacokinetic studies of curcumin.
Keywords: prostate cancer